PRZEMIANY STRUKTURY SPOŁECZNEJ, PRZESTRZENNEJ I FUNKCJONALNEJ WIELKICH OSIEDLI MIESZKANIOWYCH NA PRZYKŁADZIE OSIEDLA WIDZEW-WSCHÓD W ŁODZI - Szafrańska, Ewa (Space – Society – Economy, 2012)
Large-scale housing estates built after Second World War are often seen as a problematic areas in many cities all over Europe. This paper focuses on one of largest housing estates in Łódź – Widzew-Wschód. The purpose of the article is to describe the large housing estate Widzew-Wschód in the light of statistical data such as: age structure of population, household types, educational structure, and also living conditions and to identify and clarify the social, spatial functional and physiognomic changes which have occurred in transformation period in this estate. In this paper it is shown that the empirical studies contradict the opinion that a block housing estate is a “bad address” within the city space and an “escape” area, physically and socially degraded. The particular character of Łódź - a city with a high percentage of old, low standard flats and not very well-off inhabitants – creates conditions in which a flat in a block housing estate is still an attractive and desirable place of residence.